Divide and privatize: Firms break-up and performance - Evézen Koécenda; Jan Hanousek (Osteuropa-Institut Regensburg, 2010)
We analyze the long-term effects of divesture and ownership change on corporate performance. We employ a unique data set for a large number of Czech firms spanning the period 1996-2005. We employ a propensity score matching procedure to deal with endogeneity problems. Our results, which are generally in line with the positive effects of divestiture found in the developed-market literature, show that the initial effects of divestiture are positive but after a certain point they quickly diminish over time.
Keywords: D23; G32; G34; L20; M21; P47; 330; firm divestiture; corporate performance; ownership changes; privatization; emerging markets; endogeneity; propensity score matching procedure; Desinvestition; Privatisierung; Unternehmensentwicklung; Aufstrebende Märkte; Schätzung; Tschechische Republik